Relationship between myopia and sleep habits among the primary school students in Jiading District, Shanghai - LIN Mile; PENG Hui; YANG Feifei; XUE Junlei; YU Hongjie; MA Feifei; PENG Qian; WANG Ying; SHI Huijing (Shanghai yufang yixue)
ObjectiveTo analyze the prevalence of myopia among the primary school students in Shanghai, and to explore its relationship with sleep duration and sleep quality, providing references for precise myopia prevention.MethodsA cross-sectional survey and random sampling were employed. Between April and May 2023, a total of 1 889 students from grades 1 to 5 in Jiading District, Shanghai, were selected for vision testing and a questionnaire on children’s sleeping habits and relevant factors were conducted using the Children’s Sleep Habits Questionnaire (CSHQ) in Chinese. The relationship between myopia and sleep patterns was analyzed using chi-square tests and a multivariate logistic regression model.ResultsThe overall myopia rate among the primary school students in Jiading District, Shanghai, was 35.6%. The results of univariate analysis showed that in the myopia group, the incidences of sleep disturbance and sleep anxiety were lower compared to children without myopia, while the incidences of sleep continuity and parasomnias were higher than there in the non-myopia group (χ2=12.816, 10.292, 10.971, 3.917, all P<0.05). Additionally, among the elementary school students with an average daily sleep duration of less than 10 hours, the prevalence of myopia was higher. The multivariate logistic regression analysis revealed that factors such as being female (OR=1.291, 95%CI: 1.044‒1.597), higher grade levels (2nd grade: OR=2.174, 95%CI: 1.471‒3.212; 3rd grade:OR=3.850, 95%CI: 2.648‒5.598; 4th grade: OR=8.906, 95%CI: 6.154‒12.890; 5th grade: OR=12.299, 95%CI: 8.433‒17.937), having one parent (OR=2.250, 95%CI: 1.757‒2.881) or both parents (OR=3.623, 95%CI: 2.719‒4.827) with myopia, and parasomnias (OR=1.518, 95%CI: 1.065‒2.163) were associated with a higher detection rate of myopia.ConclusionThe prevalence of myopia is notably high among the primary school students in Jiading District, Shanghai, and there is an association between the occurrence of myopia and parasomnias.